Impact of the COVID-19 pandemic on HIV care in Guatemala. (July 2021) - Medina, Narda; Alastruey-Izquierdo, Ana; Bonilla, Oscar; Ortíz, Brenan; Gamboa, Osmar; Salazar, Luis Roberto; Mercado, Danicela; Pérez, Juan C.; Denning, David W.; Arathoon, Eduardo; Rodriguez-Tudela, Juan Luis; ,; et al.
Highlights: The COVID-19 pandemic has disrupted healthcare services. In Guatemala, the COVID-19 pandemic has severely impacted human immunodeficiency (HIV) services. During the COVID-19 pandemic, deaths due to opportunistic infections increased by 10.7%. HIV testing decreased by 54.7% during the COVID-19 pandemic. Abstract: Objectives: To describe the impact of the coronavirus disease 2019 (COVID-19) pandemic on the diagnosis of human immunodeficiency virus (HIV) and deaths from opportunistic infections in Guatemala. Methods: A retrospective study was conducted to investigate the impact of the COVID-19 pandemic on people with HIV at a referral clinic (Clinica Familiar Luis Angel García, CFLAG), as well as the disruption of services at a diagnostic laboratory hub (DLH) which provides diagnosis for opportunistic infections to a network of 13 HIV healthcare facilities. Comparative analysis was undertaken using the months March–August from two different time periods: (i) pre-COVID-19 (2017–2019); and (ii) during the COVID-19 period (2020). Results: During the COVID-19 period, 7360 HIV tests were performed at Clinica Familiar Luis Angel García, compared with an average of 16, 218 tests in the pre-COVID-19 period; a reduction of 54.7% [95% confidence interval (CI) 53.8–55.4%], Deaths from opportunistic infections at 90 days were 10.7% higher in 2020 compared with 2019 (27.3% vs 16.6%; P = 0.05). Clinical samples sent to the DLH for diagnosis of opportunistic infections decreased by 43.7% in 2020 (95% CI 41.0–46.2%). Conclusion: The COVID-19 pandemic is having a substantial impact on HIV care in Guatemala. Diagnostic services for HIV have been severely affected and deaths from opportunistic infections have increased. The lessons learnt must guide the introduction of strategies to reduce the impact of the pandemic.